Answer:
x=19
Step-by-step explanation:
9*(9+15)=8*(8+x)
9*(24)=8(x+8)
216=8x+64
216-64=8x+64-64
152=8x
152/8=8x/8
19=x
x=19
Answer:
Step-by-step explanation:
1)y=-6x-14 ---------(i)
-x-3y=-9 ---------- (ii)
Substitution method:
Substitute y value in equ (i)
-x -3*(-6x-14) = -9
-x - 3*-6x -3*(-14)= -9
-x + 18x + 42 = -9
17x = -9 -42
17x = -51
x = -51/17
x = -3
Substitute x value in equation (i)
y = -6*-3 -14
y =18-14
y = 4
Answer: -6
Step-by-step explanation:
Answer:
xx=-0.8
Step-by-step explanation:
not sure if this is right because the 12xx is kind of strange
12xx+16-1=0
12xx+15=0
12xx=-15
12/12xx=12/-15
xx=-.8
Answer:
I cant see the table
Step-by-step explanation: